Keratin-72 restricts HIV-1 infection in resting CD4+ T cells by sequestering capsids in intermediate filaments - Yang He; Meng Xu; Jiayue Ouyang; Li Zhao; Tiankui Ma; Xiaowei Zhang; Ruolin Wang; Hong Shang; Guoxin Liang (Nature Communications)
Abstract The accessory protein Vpx from the red-capped mangabey or mandrill SIV (SIVrcm/mnd-2) lineage has been reported to increase HIV-1 infection in resting CD4+ T cells without affecting SAMHD1, a known target of Vpx in HIV-1 infection. This indicates that Vpx, in addition to SAMHD1, circumvents other restriction factors for lentiviruses. To identify potential restriction factors, this study examined cellular proteins interacting with Vpxrcm and found that keratin-72 (KRT72), an intermediate filament (IF) protein expressed in resting CD4+ T cells, is a host antiviral factor targeted by Vpx. Vpxrcm/mnd-2 lineages could strongly promote KRT72 degradation, resulting in increased HIV-1 infection in resting CD4+ T cells. We discovered that KRT72 restricts HIV-1 replication by sequestering incoming HIV-1 capsids in cytoplasmic IFs. With KRT72, the capsid cores of HIV-1 become attached to IFs, and their trafficking toward the nucleus is inhibited. In contrast, without KRT72, HIV-1 capsids are transported to the nucleus, leading to high levels of integrated HIV-1 DNA. Thus, KRT72 is a Vpx-counteracted antiviral factor that binds the incoming capsids to cytoplasmic IFs, restricting HIV-1 infection in resting CD4+ T cells.